Markers of hypoxia in aqueous humor as factors for assessing the severity of diabetic retinopathy (Ukrainian Journal of Ophthalmology, 2026)
Purpose. To establish the diagnostic value of lactate versus hypoxia-inducible factor (HIF)-1α concentration in the aqueous humor (AH) for determining the severity of diabetic retinopathy DR.Material and Methods. Totally, 110 type 2 diabetics with DR (110 eyes) were involved in the study and divided into five groups from no apparent retinopathy (DR0) to proliferative DR (PDR) based on the 2003 international classification. The control group included 25 non-diabetics. Lactate concentrations (mg/mL) were determined in AH samples obtained during cataract surgery, and HIF-1α concentrations (pg/mL) were determined in this cohort of patients in our previous study.Results. AH lactate level increased with disease progression (p < 0.001), with a median level ranging from 0.32 mg/mL in controls to 6.49 mg/mL in group 5 (PDR). A total accuracy was moderate (~60%) for both markers for the discrimination between all grades of the disease, but a high AH lactate concentration (>8.56 mg/mL) was found to be highly specific (98.9%) for confirming PDR. To assess the risk of DR progression, a total study sample was divided into two categories (mild-to-moderate DR vs severe DR) on the basis of AH HIF-1α concentration, and a threshold of >377 pg/mL provided for a total prediction accuracy of 71.9% and specificity 95.2%.Conclusion. AH lactate and HIF-1α concentrations reflect a gradient of hypoxic load in DR. Determining AH lactate concentrations (a rule-in marker) is effective for severe conditions, whereas determining AH HIF-1α concentrations should be used for stratifying patients into risk groups to guide planning the intensity of supervision and treatment.
Keywords: diabetic retinopathy; type 2 diabetes mellitus; acute retinal pigment epitheliitis; lactate; hypoxia-inducible factor 1α; biomarkers; aqueous humor; disease progression